Welcome to IMIA (Yearbook of Medical Informatics, 2019)
PresidentDr. Christoph Lehmann, United States (2017–2019)President electDr. Sabine Koch, Sweden (2017–201 9)Past PresidentDr. Hyeoun-Ae Park, South Korea (2017–2019)SecretaryDr. Petter Hurlen, Norway (2015–2021)TreasurerJohanna Westbrook, Australia (2017–2020)Vice PresidentsMedInfoDr. Patrick Weber, Switzerland (2017–2019)MembershipDr. Daniel Luna, Argentina (2018–2021)ServicesDr. Brigitte Seroussi, France (2016–2019)Special AffairsDr. Elizabeth Borycki, Canada (2016–2019)Working & Special Interest Groups Dr. Ying (Helen) Wu, China (2016–2019)CEOElaine Huesing, Canada IMIA Web site: www.imia.orgRegional Vice Presidents to IMIAAPAMI: Asia Pacific Association for Medical InformaticsDr. Vajira Dissanayake, Sri LankaEFMI: European Federation for Medical InformaticsDr. Christian Lovis, SwitzerlandHELINA: Pan African Health Informatics AssociationDr. Ghislain Kouematchoua Tchuitcheu, Germany/Cameroon IMIA-LAC: Health Informatics Association for Latin America and the CaribbeanMarcelo Lucio da Silva, BrazilMENAHIA: Middle East and North African Health Informatics AssociationDr. Riyad Al Shammari, Saudi ArabiaNorth American RegionAndre Kushniruk, CanadaIMIA Liaison Officers, ex officioWHO Liaison OfficerDr. Antoine Geissbuhler, SwitzerlandIFIP Liaison OfficerDr. Hiroshi Takeda, JapanISO Liaison OfficerDr. Michio Kimura, Japan